The clinical features and prognosis of the monoclonal gammopathy undetermined significance: A single center study - Ma, Ling; Xu, Shuang; Wen, Lei; Liu, Yang; Kang, Ying; Huang, Xiaojun; Lu, Jin (Blood cells, molecules, & diseases, 2018)
The aim of this study was to identify the clinical features and prognosis of monoclonal gammopathy of undetermined significance (MGUS) in China. This single center study enrolled 111 subjects visited in Peking University People's hospital including 62 males and 49 females. Among them, IgG subtype, IgA subtype and IgM subtype were 56.31%, 28.16%, 5.83% respectively. 10.7% patients had the abnormality of convectional cytogenetic testing, while the interphase fluorescence in situ hybridization (FISH) made the positive rate increased to 18.9%, and IgH rearrangement was most common. The positive rate of MAGE-C1/CT7 was 73.8% in MGUS, but the expression level was 0.33%, lower than that in MM. After a median follow-up of 15.9 months, 5 cases were determined disease progression (PD), and 1 patient had died of disease progression, two died of the complication. MGUS is becoming increasingly important in China. Male had higher prevalence of MGUS, the most common subtype was IgG, and the IgA subtype was much higher which may be related to the air pollution. MGUS patients had a high positive rate of MAGE-C1/CT7 gene, but the expression level was low. Some patients with MGUS could progress to MM, systemic amyloidosis and other malignant diseases.